Hubungan Tingkat Pendidikan Petani terhadap Serangan Hama dan Penyakit pada Budidaya Tanaman di Sumatera Selatan - Arsi, Arsi; Pratama, Rahmat; Adriansyah, Fikri; Hamidson, Harman; Tricahyati, Titi; Suparman, Suparman; Doni, Rama; Dona, Rama; Cahya, Muhardianto; Izzati, Rinaldi Fahril; Saputra, Rian; Trianda, Gita; Wahyudi, Lidya Dwi; Barokah, Putri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Arsi, A., Pratama, R., Adriansyah, F., Hamidson, H., Tricahyati, T., Suparman, S., Doni, R., Dona, R., Rinaldi Fahril Izzati, Rian Saputra, Gita Trianda, Lidya Dwi Wahyudi, Putri Barokah. (2024). The relationship of farmers' education level to pest and disease attacks in plant cultivation in South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 787–798). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The aimed of this research was to determine the behavior and understanding of farmers in using pesticides based on educational background. Pesticide is a poisonous chemical which is able to ruin human and animal health and also pollute the environment. The use of pesticide has to consider five properness i. e. proper target, proper active ingredient, proper time, proper dosage/concentration and proper equipment. Knowledge is one of factors affecting people behavior, including behavior in pesticide application. The less knowledge of farmers in pesticide application made them use too much pesticide which might cause degradation of environment and pesticide residue in agricultural products which is dangerous to consumers. Method applied in the study was an interview method using questionnaire to 180 farmers, followed by field observation in their field. 57% of respondents had Elementary School background, 20% had Junior High Scholl background, 23% had Senior High School background and one of them had university education background. The average score of pesticide use was 1,92 from farmers who graduated from bachelor, then the pesticide score of farmers who graduated from elementry school, junior high school, and high school had the same pesticide score of 2,39 and all education is categorized as good in using pesticides. The pesticide application score did not correlate with the presence of pest in the field but significanly correlate with the prsence of plant diseases. The highest plant disease intensity (26.55) was found in the farms belonged to farmers with elementary school backfround, while the lowest (6.61) was found in the field of farmer with university educational background.